Implementation of Flood Management Program Policy by The Public Works Spatial Planning Housing and Residential Areas Agency - Leonia Gitarisa; Muhammad Agus Muljanto (Univiversitas Dr. Djar Wattiheluw, 2024)
Malang City is one of the cities in East Java that has experienced a total of 700 flood events since 2019 (BPBD’s data) and has made floods a routine problem for the local government. This phenomenon is the basis for the emergence of a flood management program and this research aims to determine the implementation of flood management program policy by the Public Works, Spatial Planning, Housing, and Residential Areas Agency in Malang City. This research uses a descriptive qualitative research design to collect written data through interviews, documentation, and observation. The results show that the flood management program policy has been implemented quite well in Malang City. Efforts by the Malang City Public Works, Spatial Planning, Housing, and Residential Areas Office to provide understanding to the public regarding the urgency of handling floods through this program need to be carried out.